PTH-235 Small bowel obstruction in pregnancy is a complex surgical problem with a high risk of foetal loss. (22nd June 2015) - Webster, P; Bailey, M; Wilson, J; Burke, D
Abstract : Introduction: Small bowel obstruction (SBO) in pregnancy is rare and is most commonly caused by adhesions from previous abdominal surgery. Previous literature reviews have emphasised the need for prompt laparotomy in all cases of SBO because of the significant risks of foetal loss and maternal mortality. Since the last review, magnetic resonance imaging (MRI) and computed tomography (CT) scans have become more widely available and can determine the exact aetiology of SBO in pregnancy. We undertook a systematic review of the contemporary literature to determine if immediate laparotomy is still always necessary with the advent of these improved imaging modalities. Method: The Medline and PubMed databases were searched for cases of SBO in pregnancy between 1992 and 2014. Two cases from our own institution were also reviewed. Results: Forty-six cases of SBO in pregnancy were identified, with adhesions being the most common aetiology (50%), followed by small bowel volvulus (15%) and internal hernia (13%). The overall risk of foetal loss was 17% and maternal mortality was 2%. In cases of adhesional SBO, 91% of cases were managed surgically, with 14% foetal loss. Two cases (9%) were managed conservatively with no complications. MRI scan was used to diagnose SBO in 11% of cases and CT scan in 13% of cases. Conclusion: Based on our experience, and the contemporary literature, we recommend that if available, an urgent MRI of the abdomen should be undertaken to diagnose the aetiology of SBO in pregnancy. In cases of adhesional SBO, conservative treatment may be safely commenced, with a low threshold for laparotomy. In other causes, such as volvulus or internal hernia, prompt laparotomy remains the treatment of choice. Disclosure of interest: None Declared.